2013
DOI: 10.1017/s1355770x13000521
|View full text |Cite
|
Sign up to set email alerts
|

Policy reform of emission taxes and environmental research and development incentives in an international Cournot model with product differentiation

Abstract: This paper studies multilateral and unilateral policy reforms of environmental R&D subsidies and emission taxes in a two-country Cournot model with oligopolistic interdependence. The analysis indicates, inter alia, that there is a potential family of multilateral and unilateral policy reforms which can be set by pollution-intensive and pollution-moderate countries to reduce global emissions. In particular, the analysis suggests that a unilateral increase in the subsidy in the pollution-moderate country may red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 26 publications
(83 reference statements)
1
3
0
Order By: Relevance
“…Since we are assuming asymmetry in pollution intensities across but not within countries, changes in global emissions due to a change in k depend on asymmetries in pollution intensities across countries and changes in output within and across countries. Consistent with previous studies, an increase in the emission tax in one country lowers emissions in that country (via lower output and higher abatement induced by the tax), but raises emissions in the other country via higher output in that country (e.g., Gautier, 2013, 2014, 2017; Lahiri and Symeonidis, 2007). We summarize these results in the following remark.…”
Section: The Modelsupporting
confidence: 88%
“…Since we are assuming asymmetry in pollution intensities across but not within countries, changes in global emissions due to a change in k depend on asymmetries in pollution intensities across countries and changes in output within and across countries. Consistent with previous studies, an increase in the emission tax in one country lowers emissions in that country (via lower output and higher abatement induced by the tax), but raises emissions in the other country via higher output in that country (e.g., Gautier, 2013, 2014, 2017; Lahiri and Symeonidis, 2007). We summarize these results in the following remark.…”
Section: The Modelsupporting
confidence: 88%
“…More formally, let δk=δkfalse(γfalse) so that δk0 for βkγ0; k=h,f. Notice that this structure does not endogenize the ability of firms to become more or less pollution‐intensive, and in so doing I assume away issues about the strategic decision of firms on pollution abatement or environmental R&D, which the literature has touched on (e.g., Ulph; Montero , ; Ulph and Ulph ; Gautier , ). However, by assuming pollution intensity coefficients to depend positively on γ I introduce a new channel whereby an exogenous change in the degree of product differentiation alters emissions.…”
Section: Comparative Staticsmentioning
confidence: 99%
“…Yakita and Yamauchi (2011) studied the environmental R&D strategy of enterprises in the duopoly model with horizontal differentiation and found that when the degree of product differentiation is large, the spillover of environmental R&D cooperation technology reduces the total social emission level. Gautier (2014) studied the role of product differentiation in the environmental policy reforms of two countries and found that reductions in foreign subsidies reduce country profits, production and pollution emissions as product differentiation increases. Kugler and Verhoogen (2012) found that there is a positive relationship between the scale of the enterprise and the output price in heterogeneous industries, but this relationship does not exist in homogeneous industries.…”
Section: Literature Reviewmentioning
confidence: 99%